ANALYSIS OF BANK SOUNDNESS WITH LINEAR REGRESSION AND TIME SERIES ANALYSIS - Rakha Asyraf, Rayhan
Bank is a business entity that is closely related to people's lives and plays an important role in the sustainability of the economy in a country. In Indonesia itself, there are several types of banks that are recognized in accordance with the law, namely the Central Bank, Commercial Bank, and Rural Bank, each of which has its own function and task in improving the welfare of the community. Thus, a good bank health condition is needed so that banks can always carry out their duties smoothly. In this final project, we discuss the analysis of bank soundness using mathematical models of linear regression and time series analysis to predict bank soundness in the future. The regression model used in this task is multiple linear regression and generalized linear model. While the time series analysis model used is the ARIMA and ARIMAX models. From the results of this model, it is hoped that the analysis of the soundness of banks can be more measurable and can predict the level of soundness of banks in the future which can be used as an early warning system for banks.